Combined Therapy of Probiotic Supplementation and Rehydration Improves Blood Dehydration Parameters and Decreases Mortality of Neonatal Piglets Naturally Infected with Porcine Epidemic Diarrhea Virus: A Clinical Trial - Takio Inatomi; Takamitsu Tsukahara; Gustavo A. Romero-Pérez; Ryo Inoue (Agriculture, 2021)
Although rehydration therapy (RT) has been used to treat animals suffering from viral diarrhea, mortality among farm animals still remains high, as RT alone neither significantly minimizes the duration of the illness nor reduces the looseness of stools. As porcine epidemic diarrhea (PED) is a viral disease and PED treatments are still very limited, vaccination is the common strategy to prevent it. Thus, the aim of the present study was to test whether a combination of RT and probiotics supplementation could help to improve the mortality of suckling piglets kept in a commercial farm and naturally infected with PED virus. Piglets receiving a combination of probiotic supplementation and RT showed improved (p < 0.01) blood parameters such as base excess and bicarbonate ion concentration when compared with untreated control piglets and piglets administered with RT alone. When compared with that of control piglets, mortality during the suckling period was the lowest (p < 0.05) in piglets receiving the combined therapy, but statistically unchanged between piglets receiving either RT or RT and probiotics. Our preliminary results should motivate further research on the use of a combined rehydration and probiotics therapy to reduce mortality in piglets suffering from acute diarrhea.